On the Relationship between Attachment Styles and Attitude towards Drugs: Moderating Role of Personality Traits - Mahdieh Rahmanian; Maryam Zamani; Hooshang Alibazi (Drug Control Headquarters, Research and Education Office, 2015)
Objective: The present study aimed at investigating the moderating role of personality traits in the relationship between attachment styles and attitude towards drugs. Method: To this end, 190 first-semester students of Tehran Payam Noor University (south center) in 2013-2014 were randomly selected and requested to complete adult attachment scale, Eysenck personality questionnaire, and attitude towards drugs questionnaire. Results: The results of this study indicated that only avoidance attachment style could predict attitude towards drugs and this relationship could be significantly moderated by neuroticism. Conclusion: The results of this study can have applications and implications in the development of treatment and training programs for addiction prevention in vulnerable populations.